IRON DEFICIENCY ANEMIAS IN CHILDREN WITH GASTROINTESTINAL DISEASES - Abdukadirova Nargiza Batirbekovna (Western European Studies, 2025)
Iron deficiency anemia is a pathological condition in which the level of iron in the body, the concentration of red blood cells and hemoglobin in the blood decreases. IDA is the most common type of anemia and the most common disease in the world associated with a lack of nutrients. Iron is an indispensable element that can be obtained only with food. Often, in diseases of the gastrointestinal tract, the process of absorption of this element is disrupted, which leads to anemia. In this article we consider the pathogenesis of the development of iron deficiency anemia in pathologies of the digestive system.
Keywords: Iron deficiency anemia; gastrointestinal tract diseases